The Phenomenology Approach and Its Relevance to Historical Learning at the High School Level in the Revolutionary Era 4.0 - Ahmad Benny Syahputra; Supardi Supardi; Wahyu Noviansyah (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2021)
In essence, humans do not only rely on natural activities. Historically, humans have used their minds to think according to the dynamics of the times. Therefore, in facing the world of education in the 21st century, the development of technology and communication is a necessity as a result of the phenomenon of the industrial revolution 4.0 which brings several consequences from the field of education, especially in history learning in high school. This article aims to determine the tangent to the phenomenological approach and its relevance to history learning in high school, especially in the era of the industrial revolution 4.0. This study uses a qualitative research method with a literature study approach. Then in data collection, the authors collect and review a number of journals or literature that are still related to discussion topics such as phenomenology, history learning, and revolution 4.0. The result shows that there is relevance to the use of phenomenology as an approach in history learning as a method in spurring students' ability to think critically, creatively, and effectively towards developing phenomena by integrating technology into history learning as an effort to face revolution 4.0. Keywords: Phenomenology Apporach, Historical Learning, Revoluionary Era 4.0